Perfil dos usuários e uso dos acervos das bibliotecas dos Centros Educacionais Unificados – CEUs – São Paulo - Oliveira, Raquel da Silva (2018)
This work aimed to analyze the profile of the users, their literary choices and the possible increases that the creation of public libraries, in regions highly deprived of public cultural equipment, causes in the population of its surroundings, with support in the contributions of Bourdieu and Darbel (2003), primarily with regard to access to cultural assets and their relationship with the cultural capital of users. In order to do so, through a statistical series of statistical data of use, analyzed the increment of the use of the public libraries of the CEUs – Centro de Educação Unificado, from the City Hall of São Paulo, from 2006 to 2017. Created in this new project of school equipment, libraries were planned not only to serve it, but also to promote the use of the whole community around it in which practically the totality of the 46 units is located in neighborhoods of the urban periphery. As indicators of the users' profile and the use of the units, the data referring to age, sex and level of schooling were collected and organized in tables and graphs, crossing them with the type of literature they are looking for (children's literature, literature in general, books didactic and reference works). The main findings were: expressive growth of loans in the period, predominantly by white, female and with at least minimum elementary education